DEVELOPMENT MODEL OF PASRAMAN KILAT LEARNING TO IMPROVE THE SPIRITUAL VALUES OF HINDU YOUTH - I Ketut Sudarsana (SCAD Independent, 2016)
Human resource development is one that can be implemented through the implementation of non-formal education, in this case is pasraman kilat which is expected to enhance the spiritual values. Methodologically this study is using the procedure of research and development, where the stages include: (1) A preliminary study, (2) Preparation of a conceptual model, (3) Validation and revision of the model, (4) Testing the model, (5) Revision of the model, and (6) The final model of pasraman kilat. This study managed to describe (1) The pasraman kilat has not fully follow the principles of good learning, such as planning, implementation and evaluation. (2) The conceptual model was developed using pasraman kilat participatory approach which is expected to bring about change in the planning, implementation and evaluation. (3) Implementation of pasraman kilat model is showing success. It is characterized by the achievement of such indicators; a) planning, b) implementation and c) evaluation. The effectiveness of pasraman kilat models indicated by the positive impact of both the participants and the organizers of pasraman kilat.